LMD-12. Ubiquitin Conjugating Enzymes promote leptomeningeal dissemination and decrease survival in patients with brain metastatic disease. (9th August 2021) - Paisana, Eunice; Cascão, Rita; Custódia, Carlos; Qin, Nan; Picard, Daniel; Pauck, David; Carvalho, Tânia; Ruivo, Pedro; Pereira, Pedro; Roque, Rafael; Pimentel, José; Miguéns, José; et al.
Abstract: The dissemination of cancer cells to the brain parenchyma (brain metastases - BMs) and to the leptomeninges (leptomeningeal dissemination – LD) are a late-stage complication of systemic cancers, with a poor survival. Despite advances in radiation and chemotherapy, including intrathecal administration of anticancer agents, these forms of advanced cancer are incurable. Therefore, there is an unmet clinical need for novel effective therapies that target both parenchymal and leptomeningeal disease. We analysed the transcriptomic profile of BMs from patients with diverse primary tumors, treated at CHULN, to identify genetic drivers of cancer cell dissemination to the brain and potential novel targets for therapy. The most differentially expressed gene codifies a ubiquitin conjugating enzyme (UCE). UCE levels were evaluated in tissue microarrays of BMs from an independent cohort of patients and correlated with clinical data. UCE functional role was assessed in vitro and in vivo using modulated lung and breast cancer cell lines. A high-throughput drug screening was performed to find UCE-targeting compounds. High protein levels of the UCE were associated with decreased survival in patients with BMs, independently of the primary tumor origin. High levels of UCE led to increased migration and invasion abilities in cancer cell lines in vitro, with no effect in proliferation. In vivo, high levels of UCE increased leptomeningeal dissemination and decreased survival in orthotopic models of breast cancer BMs. Leptomeningeal disease promoted by UCE was prevented by oral administration of inhibitor A, identified in our high-throughput drug screening. In conclusion, we have identified UCE as a prognostic marker in patients with BMs from different primary tumors. In orthotopic mouse models of the disease, UCE led to a worse survival and promoted leptomeningeal dissemination. Strikingly, this aggressive disease phenotype was prevented by oral therapy with inhibitor A.